2009
DOI: 10.1306/12220808082
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic controls on a salt-withdrawal intraslope minibasin, north-central Green Canyon, Gulf of Mexico: Implications for misinterpreting sea level change

Abstract: Three-dimensional seismic data from the Fuji basin, a saltcontrolled intraslope minibasin in north-central Green Canyon, Gulf of Mexico, reveal complex interactions between gravity-and suspension-driven sedimentation. Seismic volumes for late Pleistocene (∼470 ka) to Holocene fill within the Fuji basin consist of approximately 45% mass transport complexes (MTCs), 5% channelized sandy turbidites, and 50% hemipelagites and muddy turbidites. At least ten MTCs within the Fuji basin flowed radially toward its depoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 47 publications
5
60
0
Order By: Relevance
“…Short remobilisation distances are also supported by the relative position of the studied MTDs, which occur on ridge flanks and in 19 specific locations in the salt-withdrawal basin, in contrast to the remobilised deposits that pond at the centre of the minibasins (Madof et al, 2009). …”
Section: Factors Influencing Type 1 and Type 2 Mtdsmentioning
confidence: 73%
See 2 more Smart Citations
“…Short remobilisation distances are also supported by the relative position of the studied MTDs, which occur on ridge flanks and in 19 specific locations in the salt-withdrawal basin, in contrast to the remobilised deposits that pond at the centre of the minibasins (Madof et al, 2009). …”
Section: Factors Influencing Type 1 and Type 2 Mtdsmentioning
confidence: 73%
“…Type 2 MTDs are represented in the study area by MTDs C and SF1, which show very similar internal characters i.e., present slabs in a generally convergent, frontally confined flow. Other published examples of Type 2 MTDs have been observed around salt ridges in West Africa (Maia et al, 2015), in the Gulf of Mexico (Posamentier and Martinsen, 2011;Madof et al, 2009), and in lacustrine settings (Moernaut and de Batist, 2011).…”
Section: Bi-modal Mtd Types In Confined Minibasinsmentioning
confidence: 90%
See 1 more Smart Citation
“…templates, such as tortuous corridors (Smith, 2004a;Hay, 2012), mini-basins (Booth et al, 2003;Beaubouef and Abreu, 2006;Madof et al, 2009;Pirmez et al, 2012;Prather et al, 2012b;Oluboyo et al, 2014;Doughty-Jones et al, 2017), and piggy-back basins/foredeep margin slopes , and/or do not span multiple large-scale sea-level cycles (e.g., Beaubouef and Abreu, 2006;Barton, 2012). Moreover, these studies do not investigate the long-term stratigraphic evolution of slopes nor characterize stratigraphic architecture at a scale that resolves relationships between sedimentary processes and seabed topography.…”
Section: Terminal Basin Floor Lobesmentioning
confidence: 99%
“…Although, for obvious industrial reasons, turbidites have received the most attention during the past decades, the more recent acquisition of high-resolution three-dimensional (3-D) seismic data has shown that many slope and abyssal systems comprise a very significant portion of MTCs. In some settings around the world, up to 70-90% of the entire slope and deepwater stratigraphic record is composed of MTCs and associated deposits (Canals et al, 2004;Newton et al, 2004;Moscardelli, 2007;Madof et al, 2009;Beaubouef and Abreu, 2010;Posamentier and Martinsen, 2011). Although numerous geoscientists use the terms MTDs and MTCs interchangeably, in this study we define a MTC as a depositional architectural complex comprised of several coeval or closely chronological-and genetically-related masstransport deposits (MTDs)-i.e.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%